Inceptisol surface diagnostic horizons and use of δ13C as an additional attribute in the soil classification - Dortzbach, Denilson; Pereira, Marcos Gervasio; Vianna, Luiz Fernando Novaes; Gonzáles, Antonio Paz (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate superficial diagnostic horizons and to quantify δ13C in Inceptisol profiles on the highlands of the state of Santa Catarina, Brazil, as well as to propose the complementary use of this attribute in the Brazilian System of Soil Classification (SiBCS). Samples of superficial horizons were collected to characterize physical and chemical attributes of 24 modal profiles. For the evaluation of δ13C, the samples were taken at the layers of 0.0–0.10, 0.10–0.20, 0.20–0.30, 0.30–0.40, 0.40–0.50, 0.50–0.60, 0.60–0.80, and 0.80–1.00 m. Haplic Inceptisols with moderate A superficial diagnostic horizon and high total organic carbon (TOC) content predominated. The high TOC values, however, were often not enough to classify the superficial horizon as humic A, due to its small thickness. In soils with humic A, δ13C values revealed little alteration in the isotopic signature, which indicates vegetation maintenance; whereas in the soils with moderate A, alterations occurred due to cultivation. The use of δ13C to complement the SiBCS is suggested, and depth should be disregarded for classification in the case of: changes in land use in areas with slopes above 8%, shallow or small-depth soils, clayey to very clayey texture, and TOC contents above 3%.